[N i] 10400/10410 Å Lines as Possible Disk Wind Tracers in a Young Intermediate-mass Star - Haruki Katoh; Chikako Yasui; Yuji Ikeda; Naoto Kobayashi; Noriyuki Matsunaga; Sohei Kondo; Hiroaki Sameshima; Satoshi Hamano; Misaki Mizumoto; Hideyo Kawakita; Kei Fukue; Shogo Otsubo; et al. (The Astrophysical Journal, 2024)
In this study, we performed high-resolution near-infrared (NIR) spectroscopy ( R = 28,000; λ = 0.90–1.35 μ m) with a high signal-to-noise ratio on HD 200775, a very young (∼0.1 Myr old) and massive intermediate-mass star (a binary star with a mass of about 10 M _⊙ each) with a protoplanetary disk. The obtained spectra show eight forbidden lines of three elements: two of [S ii ] (10289 and 10323 Å), two of [N i ] (10400 and 10410 Å), and four of [Fe ii ] (12570, 12946, 12981, and 13209 Å). This is the first time that the [N i ] lines are detected in a young stellar object with a doublet deblended. Gaussian fitting of the spectra indicates that all line profiles have low-velocity components and exhibit blueshifted features, suggesting that all lines originate from the disk winds (magnetohydrodynamic disk wind and/or photoevaporative wind). Based on the fit, the [N i ] and [Fe ii ] lines are categorized into narrow components, while the [S ii ] lines are at the boundary between broad and narrow components. These forbidden lines are suggested to be very promising disk wind tracers among the existing ones because they are in the NIR-wavelength range, which can be observed from early stages with high sensitivities. Among these lines, [N i ] lines would be a rather powerful probe for deriving the basic physical parameters of disk wind gases. However, the study of these lines herein is limited to one object; thus, further studies are needed to examine their properties.